2013
DOI: 10.1080/01635581.2013.850966
|View full text |Cite
|
Sign up to set email alerts
|

Anticarcinogenic Effects of the Ethanolic Extract ofSalix aegyptiacain Colon Cancer Cells: Involvement of Akt/PKB and MAPK Pathways

Abstract: The bark from Salix species of plants has been traditionally consumed for its antiinflammatory properties. Because inflammation frequently accompanies the progress of colorectal cancer (CRC), we have evaluated the anticancer properties of the ethanolic extract from the bark (EEB) of S. aegyptiaca, a Salix species endogenous to the Middle East, using HCT-116 and HT29 CRC cell lines. Fresh bark from S. aegyptiaca was extracted with ethanol, fractionated by solvent-solvent partitioning and the fractions were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…18 The blockage of the AKT pathway possesses anti-tumorigenic effects in CRC cells and provides a potential strategy for CRC treatment. [32][33][34] As a negative regulator of the AKT pathway, PTEN is downregulated in CRC 20 and serves as a tumor suppressor in CRC. 21 Herein, consistent with earlier findings, TRIM14 overexpression increased p-AKT levels and decreased PTEN levels in CRC cells ( Figure 5).…”
Section: Dovepressmentioning
confidence: 99%
“…18 The blockage of the AKT pathway possesses anti-tumorigenic effects in CRC cells and provides a potential strategy for CRC treatment. [32][33][34] As a negative regulator of the AKT pathway, PTEN is downregulated in CRC 20 and serves as a tumor suppressor in CRC. 21 Herein, consistent with earlier findings, TRIM14 overexpression increased p-AKT levels and decreased PTEN levels in CRC cells ( Figure 5).…”
Section: Dovepressmentioning
confidence: 99%
“…The involvement of this pathway in the development of colon cancer and metastasis, including cell proliferation, apoptosis and migration, has been extensively investigated (15)(16)(17)(18). Furthermore, the blockade of PI3K/Akt activity in colon cancer cells has shown promising anti-cancer effects (19)(20)(21)(22). Recent studies have demonstrated that the downstream factor of the PI3K/Akt pathway, the mammalian target of rapamycin (mTOR), is a potential therapeutic target in various types of cancer, including non-small cell lung cancer (23) (26), non-Hodgkin's lymphoma (27) and leukemia (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…9 . Some recent reports showed anticancer activity of bark extract of S. aegyptiaca against human colon cancer cell lines and mouse model 10,11,12 .…”
Section: Issn: 2250-1177mentioning
confidence: 99%
“…The underlying mechanisms related to anticancer efficacy of S. aegyptiaca bark extract are yet to be explored, however some studies showed that the inhibition of colon cancer cells proliferation was mediated through G1/S cell cycle arrest and induction of apoptosis through p53 dependent pathway. Other pathways include the inhibition of PI3K/Akt and MAP Kinase pathways, and inhibition of epithelial to mesenchymal transition with the treatment of S. aegyptiaca bark extract 11,12 . Ethanolic extract of S. aegyptiaca bark exhibited chemopreventive efficacy against 1,2-dimethylhydrazine induced colon carcinogenesis in mice through antioxidant and antiinflammatory activities 10 .…”
Section: S Aegyptiaca Bark Extract Decreases the Cancer Cell Viabilitymentioning
confidence: 99%